Developing and validating an instrument to measure EFL teachers' self-reported use of productive feedback. (November 2022) - Amini, Mina Abdolhosseinzadeh; Kruger, Corne G.; Nel, Carisma
Abstract: The crucial role of teacher productive feedback in supporting communicative competence of Iranian EFL learners calls for research on measuring teacher productive feedback. The paper therefore reports on the development and validation of an instrument for measuring EFL teachers' self-reported productive feedback practices. The process of the instrument design consisted of two phases. Phase one dealt with grounding the instrument development in a rigid review of the literature, strengthening face and content validity and an initial pilot study followed by the refining of the instrument. Phase two entailed a second pilot study to confirm the face and content validity of the instrument before the final implementation of the instrument and consequent confirmation of the construct validity based on the data collected. For the two pilot studies as well as for the eventual implementation of the instrument, quantitative data were collected from Iranian EFL teachers from private language institutes. The results confirm the validity and reliability of the self-designed instrument and pave the way for further refining of the instrument and the opportunity for contextualising the instrument in future research. Highlights: Productive feedback is the process whereby the teacher provides information to learners about their performance, where this information aims to support understanding so that learners can use it to progress toward the learning goal. An instrument for measuring EFL teachers' self-reported productive feedback was developed and validated in two phases. The self-designed instrument is grounded in features of productive feedback. The development of the instrument also considered the role of the teacher in creating an environment that includes active learning by learners. The validation of the instrument paves the way for its implementation in correlation studies.